2021
DOI: 10.1016/j.bj.2020.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals against SARS-CoV as potential drug leads

Abstract: The newly emerged SARS-CoV-2 strains from the coronavirus (CoV) family is causing one of the most disruptive pandemics of the past century. Developing antiviral drugs is a challenge for the scientific community and pharmaceutical industry. Given the health emergency, repurposing of existing antiviral, antiinflammatory or antimalarial drugs is an attractive option for controlling SARS-CoV-2 with drugs. However, phytochemicals selected based on ethnomedicinal information as well as in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 48 publications
(93 reference statements)
0
32
0
Order By: Relevance
“…In the meantime, worldwide laboratories share a massive amount of genomic information, which is most difficult to analyze without bioinformatics tools. Additionally, project many potential drugs and natural products against SARS-CoV-2 with the CADD platform [ 18 , 79 , 98 , 99 , 100 ]. At present, several tools and databases of bioinformatics are available for gene analysis to vaccine/drug development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the meantime, worldwide laboratories share a massive amount of genomic information, which is most difficult to analyze without bioinformatics tools. Additionally, project many potential drugs and natural products against SARS-CoV-2 with the CADD platform [ 18 , 79 , 98 , 99 , 100 ]. At present, several tools and databases of bioinformatics are available for gene analysis to vaccine/drug development.…”
Section: Resultsmentioning
confidence: 99%
“…Mostly, systematic computational screening is the most cost−effective and resource-saving approach towards select the ‘lead’ candidate(s) in the current drug development module [ 18 , 23 , 89 , 101 ]. Overall, bioinformatics tools continuously explore hidden genomic information and mainly identified potential natural lead candidates from different sources against SARS-CoV-2 for further experimental study and validation [ 14 , 100 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies have fallen short of proving a preventive or therapeutic role for these phytochemicals against COVID19 infection in real-time. Nevertheless, they provide strong evidence that they can serve as potential lead molecules for either the therapy or the prevention of SARS-CoV-2 infection as well as other viral infections that might emerge in the future (Swain et al, 2021).…”
Section: Covid-19 Virus and Its Life Cyclementioning
confidence: 99%
“…Based upon the viral-mediated inflammatory responses and diagnosis, there are many conventional drug trials ongoing which target the viral structural and nonstructural proteins, in addition to targeting ACE2 and other cytokines (Sanders et al, 2020). It has been earlier reported that the plant metabolites like alkaloids, terpenoids, flavonoids, and lignins (Table 2) have shown their antiviral effects against rotavirus, influenza virus, dengue virus, hepatitis virus, and MERS-CoV as well as SARS-CoV (Swain et al, 2020) (Ghildiyal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%